Kematangan Gonad dan Fekunditas Ikan Gelodok (Mudskipper), Periopthalmus variabilis Eggert, dari Pantai Pulau Rupat - Nasution, Syafruddin; Ghalib, Musrifin; Parnanda, Ario (Fakultas Perikanan dan Kelautan Universitas Riau, 2016)
Mudskipper or Periopthalmus variabilis Eggert (subfamily Oxudercinae, Gobiidae) commonly present in the intertidal area of mangrove ecosystem. This fish is able to walk in the forest floor by using its pectoral fins. To understand the gonad development and fecundity of the fish, a study has been conducted in September - October 2014. The fish was sampled by scoop net at night. Results shown that the male-female ratio 2 : 1. The males were in the 1st to 4th maturity levels , while those of the females were in the 3rd, 4th and 5th levels. The fecundity was ranged from 112,496 – 137,698 eggs/fish.